أوجه الدلالة في استنباط المذهب الإباضي في العقيدة على ضوء معياري القصدية والمقبولية لدى روبرت دي بوجران = Forms of meaning in the Ibadhi Sect’s method of deduction of their doctrine of belief in the light of the acceptability and intentionality standards of Robert de Beugrande = Bentuk makna dalam metod merumuskan hukum Mazhab Ibadhi dalam permasalahan aqidah dalam konteks piawaian kesengajaan dan penerimaan mengikut Robert de Beugrande - Ali, Asem Shehadeh Saleh; Saʽīd al-Dahgīshiyyah, Su'ad (Department of Arabic and Linguistic Studies, KIRKHS, International Islamic University Malaysia, 2018)
يعد تطبيق معايير النصية لدى روبرت دي بوجراند في تحليل الخطاب العربي من توجهات قراءة النص قراءة نصية تتعلق بالمتكلم والمتلقي وصياغة النص، والأبعاد الزمانية والمكانية المحيطة به، والمذهب الإباضي من المذاهب الإسلامية التي لم يتناولها الباحثون تناولاً شاملاً؛ ولذا سوف يقوم هذا البحث بالدراسة والتحليل لقضيتين من قضايا العقيدة في المذهب الإباضي؛ وهما: تنزيه الله عن مشابهة المخلوقات، والاستواء، وذلك بتوظيف معياري القصدية والمقبولية لدى روبرت دي بوجراند في الأدلة التي استند إليها علماء المذهب الإباضي للاستدلال على رأيهم العقدي فيها، ويهدف البحث إلى تعريف الآخرين بأهم الركائز التي يرتكز إليها علماء المذهب الإباضي في آرائهم العقدية؛ ما يعمل على تقريب وجهات النظر بين المذاهب الإسلامية، ولا سيما أن البحث لم يسبق بدراسة تأصيلية لتحليل القضايا العقدية في المذهب الإباضي في ضوء معياري القصدية والمقبولية، وقد خلص البحث إلى نتيجة مفادها أن المتلقي الإباضي قد انطلق من معهود الخطاب العربي لفهم قصدية النصوص الشرعية؛ ما كان له الأثر في مقبولية النصوص والتوجيه العقدي لديهم. ******************************************************** The application of standards of textuality of Robert de Beugrande in analyzing Arabic discourse is one of the trends of reading textually a certain text that is related to the sender, the receiver and the expression of text. This would also include the spatio temporal aspects that surround it. The Ibadhi sect is among the Islamic sects which has not been given comprehensive treatment; therefore, this study will analyze two issues among the issues related to the doctrine of belief of the Ibadhi sect: the dissociation of Allah with any similarity with the creations and the issue of settling on the throne. This will be done by applying the standards of intentionality and acceptability proposed by de Beugrand on the proofs forwarded by the scholars of Ibadhi as arguments of their belief. The study also intends to put forward to the others the most important underpinnings that the Ibadhi scholars committed themselves to. This would help to close the gap between the different sects especially that the study of this nature has not been done by looking at the traditional sources to analyze the issues related to the doctrine of belief of the Ibadhi sect but rather in the context of intentionality and acceptability. The study concludes that the Ibadi receiver has begun to form the norms of the Arabic discourse to understand the intentionality of the religious text that has its influence on the acceptability of the texts and their belief trend. ********************************************************* Penggunaan piawaian tekstualiti Robert de Beugrande dalam menganalisa wacana bahasa Arab ialah satu daripada trend untuk membaca secara tekstual sesuatu teks itu yang berkaitan dengan penghantar, penerima dan kandungan teks tersebut. Mazhab Ibadhi ialah antara mazhab-mazhab Islam yang masih belum lagi mendapat perhatian akademik yang sepatutnya. Oleh kerana itu, kajian ini akan menumpukan terhadap dua isu yang berkait dengan masalah akidah iaitu isu tmensucikan Allah daripada sebarang sifat makhluq dan isu bersemayam di atas arasy. Ini akan dilaksanakan dengan menaplikasi piawaian kesengajaan dan penerimaan sebagaimana yang dicadangkan Beugrande ke atas bukti-bukti yang dikemukakan oleh para Ulamak Ibadhi sebagai hujah pegangan aqidah mereka. Kajian ini juga bermatlamat untuk mengemukakan kepada yang lain-lain asas-asas yan gmenjadi landasan mazhab ini. Ini diharap akan dapat merapatkan jurang antara mazhab kerana kajian ini tidak bersandar kepada sumber tradisional tetapi kepada sesuatu yang baharu berkenaan dengan piawaian tekstualiti. Rumusan kajian mendapati mazhab Ibadhi menggunakan norma wacana teks Arab untuk memahami maksudnya dan ini seterusnya mempengaruhi penerimaan teks dan juga kepercayaan aqidah mereka.